CODE SWITCHING IN PUELLA YOUTUBE CHANNEL - Bryan Kenny Macpal; Andriyani Marentek; Arter Jodi Senduk (Paratext: International Journal of Language and Literature, 2026)
This article, entitled “Code Switching in Puella YouTube Channel”, aims to identify, analyze, and describe the types of code switching and the reasons for their use in ten selected episodes of the Puella YouTube Channel. The study employs a descriptive qualitative method. Bullock and Toribio’s (2009) theory is used to classify types of code switching, while Holmes' (2013) theory is used to analyze the reasons. The findings show three types of code switching: 620 instances of intra-sentential switching, 392 instances of inter-sentential switching, and 131 instances of tag switching total of all is 1,143. The analysis of the reasons shows that 265 lines contain functions related to identity and relationships (50), status and formality (44), topic (49), quoting dialogue (19), affective function (46), rhetorical or metaphorical switching (42), and humor or playfulness (15). The results indicate that code switching in the Puella YouTube Channel is used not only for linguistic convenience but also to express social meaning and manage interpersonal communication.